Հայ-սիրիական առևտրատնտեսական հարաբերությունները (1991-2011 թթ.) - Հովհաննիսյան Արա (YSU Journal of International Affairs, 2014)
After proclaiming of independence in 1991 the Republic of Armenia undertook the process of establishing diplomatic relationships. Syria was one of the first countries with which there were established such relationships. There were signed three agreements between the Republic of Armenia and Arab Republic of Syria in Yerevan, on 30 March, 1992. One of them was the agreement on commercial-economic cooperation. There were organized a number of visits during which there were signed various agreements. There was created a significantly flexible legal base for cooperation in the sphere of commercial-economic relationships. There was also created an interstate committee that held several meetings both in Armenia and Syria. There were organized both exhibitions and business forums and a many highranking officials from both countries brought their participation in them. There were granted discounts for carrying out business projects. But independent on the efforts spent on the commercial-economic sphere in the period of 1991-2011 the desirable result was not achieved.